Methods in Tau Cell Biology - Feinstein, Stuart, 1954-; Lapointe, Nichole E. (Methods in cell biology, 2017)
Methods in Tau Cell Biology, Volume 141, the latest release in the Methods in Cell Biology series, looks at methods involved in tau cell biology. Edited by leaders in the field, this volume provides proven, state-of-art techniques and relevant historical background and theory that aids researchers with tactics for efficient design and effective implementation of experimental methodologies. Topics of note in this updated volume include sections on Recombinant tau expression and purification, In vitro MT dynamics and MT ends, Methods related to investigating tau structure and MT bundling, Neurite outgrowth and retraction, and Methods related to studying tau fragmentation.